Preceding Infections and Coagulation Biomarkers in Early-Onset Cryptogenic Ischemic Stroke - Hulsen, Barbara M.; Spiegelenberg, Janneke P.; Martinez-Majander, Nicolas; Tulkki, Lauri; Sarkanen, Tomi; Jäkälä, Pekka; Redfors, Petra; Huhtakangas, Juha; Ylikotila, Pauli; von Sarnowski, Bettina; Yesilot, Nilufer; Waje-Andreassen, Ulrike; et al. (American Heart Association, 2026)
BACKGROUND:
Infections might transiently trigger ischemic stroke through thromboinflammatory mechanisms, which may be especially relevant in young patients with cryptogenic ischemic stroke (CIS). This study assessed the association between infections, their characteristics, and coagulation biomarkers in young patients with CIS.
METHODS:
The SECRETO study is a multicenter case-control study at 19 European centers (2013–2022), enrolling first-ever patients with CIS aged 18 to 49 years and age- and sex-matched controls. Self-reported preceding infections within 3 months were assessed using a standardized questionnaire, and blood samples were collected at baseline and 3-month follow-up. The primary outcome was the association between preceding infections and CIS, analyzed using conditional logistic regression adjusted for demographic and vascular risk factors. Secondary outcomes were coagulation biomarkers (VWF [von Willebrand Factor], FVIII [factor VIII], fibrinogen, antithrombin III, and protein C) in relation to infection characteristics.
RESULTS:
Among 537 matched pairs, infections in the preceding week were associated with 2.6-fold higher CIS odds (odds ratio, 2.64 [95% CI, 1.34–5.20]) after multivariable adjustment. VWF activity was higher in cases than in controls (122 IU/mL versus 100 IU/mL; P<0.001). Within cases only, VWF activity was higher in cases with recent infections compared to those without infection (157 IU/mL versus 121 IU/mL). In controls, VWF levels did not differ by infection status. In stratified case-control analyses, each SD increase in VWF and factor VIII was linked to higher stroke odds in participants with recent infections or fever.
CONCLUSIONS:
This multicenter case-control study shows that recent infections are associated with higher odds of early onset CIS. Stratified analyses indicate that VWF and factor VIII are more strongly associated with CIS in the presence of recent infections. Future studies should further elucidate infection-related thromboinflammatory mechanisms underlying CIS, including a potential increased sensitivity to inflammatory triggers, and explore whether preventive measures could reduce risk in this population.